The effect of non-fusion dynamic stabilization on biomechanical responses of the implanted lumbar spine during whole-body vibration. (August 2020) - Fan, Wei; Guo, Li-Xin
Highlights: Dynamic fixation using the BioFlex system and anterior lumbar interbody fusion (ALIF) with rigid fixation were simulated using finite element method. Stress and strain responses of the healthy, degenerated, BioFlex and ALIF models to vertical vibration loading were computed. Biomechanical differences among these four finite elements models were compared. Abstract: Background and objective: Non-fusion dynamic stabilization surgery is increasingly popular for treating degenerative lumbar disc disease. However, changes in spine biomechanics after application of posterior dynamic fixation devices during whole-body vibration (WBV) remain unclear. The study aimed to examine the effects of non-fusion dynamic stabilization on biomechanical responses of the implanted lumbar spine to vertical WBV. Methods: By modifying L4–L5 segment of the healthy human L1–sacrum finite element model, single-level disc degeneration, dynamic fixation using the BioFlex system and anterior lumbar interbody fusion (ALIF) with rigid fixation were simulated, respectively. Dynamic responses of stress and strain in the spinal levels for the healthy, degenerated, BioFlex and ALIF models under an axial cyclic loading were investigated and compared. Results: The results showed that endplate stress at implant level was lower in the BioFlex model than in the degenerated and ALIF models, but stress of the connecting rod in the BioFlex system was greater than that in the rigid fixation system used in the ALIF. Compared with the healthy model, stress and strain responses in terms of disc bulge, annulus stress and nucleus pressure at adjacent levels were decreased in the degenerated, BioFlex and ALIF models, but no obvious difference was observed in these responses among the three models. Conclusions: This study may be helpful to understand variations in vibration characteristics of the lumbar spine after application of non-fusion dynamic stabilization system.